Non-canonical Wnt signaling regulates cell polarity in female reproductive tract development via van gogh-like 2 - vandenBerg, Alysia L. (Company of Biologists, 2009)
Wnt signaling effectors direct the development and adult remodeling of the female reproductive tract (FRT); however, the role of non-canonical Wnt signaling has not been explored in this tissue. The non-canonical Wnt signaling protein van gogh-like 2 is mutated in loop-tail (Lp) mutant mice (Vangl2(Lp)), which display defects in multiple tissues. We find that Vangl2(Lp) mutant uterine epithelium displays altered cell polarity, concommitant with changes in cytoskeletal actin and scribble (scribbled, Scrb1) localization. The postnatal mutant phenotype is an exacerbation of that seen at birth, exhibiting more smooth muscle and reduced stromal mesenchyme. These data suggest that early changes in cell polarity have lasting consequences for FRT development. Furthermore, Vangl2 is required to restrict Scrb1 protein to the basolateral epithelial membrane in the neonatal uterus, and an accumulation of fibrillar-like structures observed by electron microscopy in Vangl2(Lp) mutant epithelium suggests that mislocalization of Scrb1 in mutants alters the composition of the apical face of the epithelium. Heterozygous and homozygous Vangl2(Lp) mutant postnatal tissues exhibit similar phenotypes and polarity defects and display a 50% reduction in Wnt7a levels, suggesting that the Vangl2(Lp) mutation acts dominantly in the FRT. These studies demonstrate that the establishment and maintenance of cell polarity through non-canonical Wnt signaling are required for FRT development.